Objectives of and barriers to innovation: How do they influence the decision to innovate? - María Beatriz Corchuelo Martínez-Azúa; Celia Sama-Berrocal (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study focuses on the analysis of the innovation activity of agribusiness in Extremadura (Spain). Using as main variables the objectives of and barriers to innovation perceived by agri-food companies, its objective is threefold: (1) to analyse how the objectives of and barriers to innovation influence the companies' willingness to innovate and competitiveness; (2) to investigate how innovation objectives (strategies) influence the type of innovation developed; (3) to study how barriers to innovation influence the demand for several public actions. The data used for this study were taken from an ad hoc questionnaire sent to agri-food companies from Extremadura during the months of February to April 2021. The results show the influence of the objectives and barriers on the variables analysed (willingness to innovate and competitiveness, types of innovation, and demand for government actions). Specifically, uncertainty and lack of knowledge are barriers that negatively influence the willingness to innovate. Innovative strategies aimed at reducing costs, respecting regulations and the environment, focusing on production and demand, and expanding the market have a positive influence both on the willingness to innovate and competitiveness. The types of innovation developed (product, process, commercial, organizational) were related to various innovative strategies based on the pursued objectives. Finally, evidence is provided by the barriers that lead companies to request specific actions from public administrations. These results may be useful both for managers of agri-food companies and for public administrations, especially at the regional level, in the design of public policies and actions aimed at encouraging innovation in this industry sector.
Keywords: 650; agri-food industry; competitiveness; demand for government actions; obstacles to innovation; type of innovation; willingness to innovate